Conversações espontâneas em ELE: a roda de conversa na perspectiva da análise da conversação e das crenças dos seus participantes - Torres, María Cristina Maldonado (2019)
Oral interactions in foreign languages (FL) in the classroom are essential for the acquisition of the language under study. Oral interaction in the foreign languages is one of the main elements in the teaching and learning process because, besides facilitating learning, it determines the quality of the process (BARBIRATO, 2016). Although the importance of oral practices in classes of foreign languages has been highlighted in recent decades, the creation of spaces in which students and teachers can interact freely in FL continues to be a challenge for teacher training courses. Therefore, the conversation rounds were created to be spaces that met the demands of oral practice in foreign language through free and spontaneous conversations. In this context, the present research aims to analyze the conversations developed in the project Conversation Rounds, carried out with a class of the Spanish Foreign Language course (SFL) of the Federal University of Santa Maria (UFSM) in the first semester of 2017. This is a qualitative research based on the studies of Marcuschi’s Conversation Analysis (2005), and on the study of the relationship between beliefs and learning, according to Barcelos (2000, 2001, 2004, 2010, 2011 and 2013) and Silva (2007, 2011), prioritizing the contextual approach to beliefs. The theoretical framework are also based on Vygotsky’s (1998) social interaction perspective, and on the Barbirato’s (2005, 2016) approach on classroom interactions in foreign language. For the data collection, questionnaires, semi-structured interviews and filming of the Conversation Rounds meetings were used. The results indicate that the conversations produced in the Conversation Rounds in FL are configured as conversations similar to those that take place outside the classroom, giving students opportunities to interact in the foreign language. The hypothesis of the research that the Conversation Rounds is a communicative environment, capable of enabling spontaneous conversations in the classroom, was confirmed by two ways: a) through the Analysis of the Conversation made from the observation and examination of the filming of the meetings; b) from the perspective of students based on their beliefs about the project.